Incidence of seroma in sublay versus onlay mesh repair of incisional hernia - Ibrahim, Rashid (Ann Med Surg (Lond), 2020)
A best evidence topic has been constructed using a described protocol. The three-part question addressed was: In patient undergoing open mesh repair of incisional hernia, is there any difference in the rate of seroma between Sublay and Onlay technique? The best evidence showed that Sublay repair has a lower seroma rate in comparison to onlay repair.